The Effect of Counseling Video on Breast Cancer Early Detection Behavior in SMAN I Golewa Barat, Ngada Regency - Maria Marselina Meo; Deviarbi Sakke Tira; Indriati A. Tedju Hinga (Lontar : Journal of Community Health, 2022)
Breast cancer is a malignant tumor formed from breast cells that grow and spread between tissues or organs near the breast or other body parts. One of the control and prevention programs for breast cancer is Breast Self-Examination (BSE). BSE is a breast examination that women can carry out continuously for a month. It is an examination in early detection of the possibility of an abnormal bulge (lump) in the breast. The purpose of this Studi was to analyze The Effect of BSE Counseling Using Video on The Knowledge, Attitudes, and Behavioral Practices of Early Detection of Breast Cancer in XII Class students of SMAN I Golewa Barat Ngada Regency 2020. This study used the pre-experimental method with one group pre-test and post-test design. The sample in this study was all students from the XII class of SMAN I Golewa Barat (136 students). Data were analyzed using Wilcoxon's test. Based on the results of the study, there was an influence between BSE counseling with knowledge (p=0.000), attitudes (p=0.000), and behavior for early detection of breast cancer (p=0.000). Schools should cooperate with the local health center or health office to carry out health education on an ongoing basis, especially BSE and breast counseling to students to prevent cancer early and reduce breast cancer mortality and morbidity.